2013
DOI: 10.3389/fphys.2013.00121
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers associated with osteoarthritis after destabilization surgery in young mice with and without Receptor for Advanced Glycation End-products (RAGE)

Abstract: HtrA1, Ddr-2, and Mmp-13 are reliable biomarkers for osteoarthritis (OA), yet the exact mechanism for the upregulation of HtrA-1 is unknown. Some have shown that chondrocyte hypertrophy is associated with early indicators of inflammation including TGF-β and the Receptor for Advanced Glycation End-products (RAGE). To examine the correlation of inflammation with the expression of biomarkers in OA, we performed right knee destabilization surgery on 4-week-old-wild type and RAGE knock-out (KO) mice. We assayed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
4
25
1
1
Order By: Relevance
“…Additionally, RAGE KO mice experienced a dose-dependent increase in both TGF-B1 and HtrA1 upon TAK-242 treatment, a finding which is contrary to our previous results which showed a reciprocal relationship between these two biomarkers [3]. These data could indicate that a shared downstream product of the RAGE and TLR-4 is responsible for HtrA1 induced inhibition of Tgf-B1.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Additionally, RAGE KO mice experienced a dose-dependent increase in both TGF-B1 and HtrA1 upon TAK-242 treatment, a finding which is contrary to our previous results which showed a reciprocal relationship between these two biomarkers [3]. These data could indicate that a shared downstream product of the RAGE and TLR-4 is responsible for HtrA1 induced inhibition of Tgf-B1.…”
Section: Discussioncontrasting
confidence: 57%
“…Our previous studies have demonstrated that even when RAGE is knocked out, TGF-B levels are not significantly different from wild type (WT) mice [3]. This observation suggests an alternate transduction mechanism that results in production of Tgf-B.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…It has also been shown that inflammation can be related to the onset of OA [24][25][26]. Inflammation is associated with the upregulation of HtrA1 which degrades aggrecan and other proteoglycans in the pericellular matrix (PCM) [27].…”
Section: Introductionmentioning
confidence: 99%